Prospects of molecular genetic approaches in controlling technological properties of wheat grain in the context of the "grain – flour – bread" chain - E. K. Khlestkina; T. A. Pshenichnikova; N. I. Usenko; Yu. S. Otmakhova (Вавиловский журнал генетики и селекции, 2016)
The potential of molecular approaches in the management of the technological properties of wheat grain affecting the quality of the end product of bread industry is considered. Currently, along with the growth of grain production, the traditional range of staples is crowded out, the quality of most popular bread varieties deteriorates, and dozens of different substances of biological and chemical origin are used as bread improvers. Meanwhile, the genetic potential of wheat allows the development of varieties with technological parameters of grain suitable for production of high-quality bread. In Russia, multiple examples of the creation of varieties for the production of first and second-class grain are known, and modern molecular genetics offers techniques that can supplement classical breeding approaches and accelerate the development of new varieties adapted to the conditions and requirements of the baking industry, using the natural genetic potential of wheat. We summarize the diversity of requirements for grain and flour for different end-use products. Statistics on the volume and structure of grain quality in Russia in 2011–2014 is analyzed. An essential deformation of the quality structure of the produced wheat grain in favor of less valuable classes is observed. A brief retrospective analysis of research in wheat genetics, demonstrating the contribution of genetic factors to grain and flour technological properties, is performed. Various approaches to rapid breeding of varieties with desired properties are considered in relation with the development of plant molecular genetics. The paper provides examples illustrating the feasibility of using methods of DNA diagnostics in various stages of the process, during which the genetic potential of food crops expresses itself and affects the quality of the end product. The results of molecular studies on the localization and isolation of genes determining technological properties (protein and wet gluten contents, milling properties, rheological properties, flour color, and starch properties) are reviewed. The data on diagnostic DNA markers, which are suitable for efficient selection of genotypes instead of the time-consuming analysis of technological properties during breeding process, are summarized. Thus, the information about the genetic potential of bread wheat and modern technologies that provide grounds for moving from excessive use of chemicals to a more benign and organic effect on the quality of the products throughout the "grain – flour – bread" chain, is summarized.